PERFORMANCE IN PUBLIC: INTERPERSONAL COMMUNICATION OF BEGGAR - Rahmalia Rahmalia; Teuku Zulyadi (Universitas Islam Negeri Ar-Raniry, 2019)
The interpersonal communication of beggars involves the beggars’ interaction with their donors, and interaction among beggars. This communication incorporates symbols that have been given meaning, both verbal and non-verbal. This study aims to determine the motives that encourage someone to become a beggar in Banda Aceh, the effectiveness of the city government’s policy in handling the begging activities and to find out the process of interpersonal communication of the beggars. This study applies the descriptive qualitative method with phenomenology approach, to describe the meaning of some people’s lives. The research subjects are the beggars who are willing and able to provide the required information in-depth. The result shows that the interpersonal communication process among the beggars and the beggars with the donors are conducted through symbolic interaction by using language and symbols, and role-play performance creating condition and atmosphere which gave certain meanings. The communities performing such interactions had the ability to utilise symbols to create an impression that attracted the attention of donors. The actions raised people’s sympathy who will give charities to them in any expected feedback. The understanding of this issue is important for the realization of the implementation of the regulation but still maintaining the aspirations of the citizens who uphold Islamic values, the concept of giving to the people in need.